Global research trend related to antidiabetic agent on Nigella sativa: A bibliometric analysis based on Scopus from 1987-2023 - Ahmad Azka Mahasin, Asti Arum Sari (Journal of Applied Pharmaceutical Science, 2024)
Several research studies have demonstrated the efficacy of Nigella sativa in enhancing the clinical condition associated with diabetes. However, there has been a lack of extensive use of bibliometric methods in this particular area of study. In response to this gap, we conducted a bibliometric analysis with a focus on exploring research related to N. sativa as a potential antidiabetic agent. We gathered bibliographic data from pertinent studies in the Scopus database, comprising 105 papers published between 1987 and 2023. We conducted the bibliometric analysis using Visualization of Similarities Viewer (VOSviewer) version 1.6.20. Our investigation revealed Alexandria University in Egypt as the most prolific institution, and the journal Evidence-Based Complementary and Alternative Medicine emerged as the primary publication platform for research on the antidiabetic agent of N. sativa. Egypt demonstrated notable prominence as the foremost country in both productivity and collaboration within this field. From 1987 to 2023, most studies focused on the effects of N. sativa on diabetes and how it is used to treat it. Other major issues included its immune-boosting, cardiovascular-healthy, and cancer-fighting capabilities.
Keywords: Nigella sativa, antidiabetic, bibliometrics, Scopus, VOSviewer